ANALISIS PENGARUH HARI LIBUR ISLAM TERHADAP ABNORMAL RETURN SAHAM (Studi empiris pada perusahaan yang tercatat di JII tahun 2012-2016) - Pujiadi, Bagus Wahyu; Indriani, Astiwi (Faculty of Economics and Business Diponegoro University, 2017)
There are still some differences in the results of research on the impact of holiday on stock returns. Other than that there are still few researches who only specifically examine the effects of islamics holidays against abnormal return. This research aims to analyse the influence of Islamic holiday to abnormal return of shares before and after Islamic holiday. The holidays used are Maulid Nabi, Isra’ Mi’raj, Idul Fitri, Idul Adha, and New Year Hijriyah. The study period used from 2012 to 2016.This research uses event study. Research population used all company which listed in Jakarta Islamic Index. Technique of choosing sample is used purposive sampling and obtained 15 company. The data used in this research obtained from website KSEI, website BEI, and online trading system of Mirae Asset Securities. Determination of estimated return using market adjusted model. Parametric analysis tets tools used to test the hypothesis in this study are descriptive statistic, normality tets, and paired sample t-test.The result of this study indicate that the Maulid Nabi holiday and Idul Fitri holidays affect the significant abnormal return difference between before and after the holiday. While the holidays of Isra’ Mi’raj, Idul Adha, and New Year Hijriyah hove no effect on the difference of abnormal return of stock before and after the holiday.